1991
DOI: 10.1254/jjp.56.349
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Vinpocetine against Brain Damage Caused by Ischemia.

Abstract: ABSTRACT-The effects of vinpocetine against hippocampal neuronal damage and on local cerebral blood flow (LCBF) were examined in a rat model of forebrain ischemia (10-min occlusion of the carotid arteries and hypotension). Histological evaluation of neuronal loss in the hippocampus was performed 7 days after ischemia . LCBF was measured before ischemia as well as after 2 min and 1 hr of recirculation . Vinpocetine (10 mg/kg) administered pre or post-ischemically reduced the hippocampal neuronal necrosis, while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…In vivo studies have shown that inhibition of the adenosine transporter increases extracellular adenosine 45 and attenuates ischemic damage. 6 ' 8 These results are consistent with the possibility that adenosine is formed extracellularly (by the breakdown of ATP and other adenine nucleotides released during the ischemic period), and the adenosine transporter serves to remove extracellular adenosine.…”
Section: Dipyridamole Increases Oxygen-glucosesupporting
confidence: 77%
“…In vivo studies have shown that inhibition of the adenosine transporter increases extracellular adenosine 45 and attenuates ischemic damage. 6 ' 8 These results are consistent with the possibility that adenosine is formed extracellularly (by the breakdown of ATP and other adenine nucleotides released during the ischemic period), and the adenosine transporter serves to remove extracellular adenosine.…”
Section: Dipyridamole Increases Oxygen-glucosesupporting
confidence: 77%
“…Beneficial effects on neurological symptoms have been claimed in several clinical studies [62], Recently ( fig. 5g), it has been shown that vinpocetine reduces hippocampal neuronal damage caused by transient forebrain ischemia [63] as well as after middle cerebral artery occlusion [64]. Vinpocetine clearly prevented the changes in hippocampal CMRglcand CBF values 7 days after ischemia [65].…”
Section: A Denosine Agonistsmentioning
confidence: 94%
“…Using animal models of ischemia, investigators have found neuroprotective effects from vinpocetine. Rischke and Krieglstein (1991) examined hippocampal damage in rats 7 days after experimentally induced cerebral ischemia. Among control rats, 77% of hippocampal neurons were damaged, whereas in rats given 10 mg/kg of vinpocetine (either before or after the ischemia), damage was reduced to 37% of the hippocampal neurons.…”
Section: Mechanisms and Animal Studiesmentioning
confidence: 99%